PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TALKING STICK UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN TEKS NONFIKSI TERHADAP HASIL BELAJAR SISWA DI SDN 80/I KEC. MUARA BULIAN - Natasya Agustin; Alesia Sasabila; Ulfa Ramadhani; Destrinelli; Risdalina; Irmawani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to improve students’ nonfiction reading comprehension skills through the implementation of the cooperative learning model of the Talking Stick type in Grade V at SDN 80/I, Muara Bulian District. The method used is classroom action research (CAR) conducted in two cycles. Each cycle consists of the stages of planning, implementation, observation, and reflection. Data were collected through observation, learning outcome tests, and documentation. The results show that the implementation of the Talking Stick model can improve students' learning outcomes in reading comprehension of nonfiction texts. This is evidenced by an increase in the average student score from 64.5 in cycle I to 75 in cycle II. In addition, there was an increase in students’ active participation in learning activities, especially in discussing, expressing opinions, and understanding the content of the reading. This model also creates a more enjoyable and collaborative learning atmosphere. Therefore, the cooperative learning model of the Talking Stick type is effectively used to improve nonfiction reading comprehension skills of elementary school students.